The Effects of Renal Nerve Denervation on Blood Pressure and Target Organs in Different Hypertensive Rat Models - Demin Liu; Jing Wang; Haijuan Hu; Guoqiang Gu; Rui Ding; Ruiqin Xie; Wei Cui (International Journal of Hypertension)
Background. Hypertension contributes to the progression of cardiac remodeling and renal damage. In turn, renal sympathetic hyperactivation showed elevated sympathetic nervous system activity and led to blood pressure increase in certain patients. The purpose of this study was to observe the effect of renal nerve denervation on blood pressure and target organ changes in two hypertensive rat models. Methods. Hypertensive rats were randomly divided into a renal denervation (RDN) group and sham operation group. Wistar–Kyoto (WKY) rats of the same age were set as the baseline control group. In the secondary hypertension model, SD rats were randomly divided into five groups. Blood pressure and bodyweight were measured every week until they were euthanized. Results. The two rat models underwent RDN at key timepoints. At these timepoints, the hearts and kidneys were collected for norepinephrine and angiotensin II measurements and histological analysis. Conclusion. RDN performed before development of hypertension showed a significant antihypertensive effect on the secondary hypertension model.